Folic Acid and Coenzyme Q10 Ameliorate Cognitive Dysfunction in the Rats with Intracerebroventricular Injection of Streptozotocin - Dehghani Dolatabadi, Hamid Reza (Mashhad University of Medical Sciences, 2012)
OBJECTIVE(S): The present study aimed to investigate the effects of a fat soluble antioxidant, coenzyme Q10 (CoQ10) and folic acid on learning and memory in the rats with intracerebroventricular injection of streptozotocin (ICV-STZ), an animal model of sporadic type of Alzheimer's disease. MATERIALS AND METHODS: The lesion groups were injected bilaterally with ICV-STZ (1.5 mg/kg b.wt., in normal saline). In the treated groups, rats received folic acid (4 mg/kg; i.p.) or CoQ10 (10 mg/kg; i.p.), either alone or together, for 21 days. Passive avoidance learning test was used for evaluation of learning and memory. RESULTS: The results showed that learning and memory performance was significantly impaired in the rats with ICV-STZ (P< 0.001), however CoQ10 and folic acid, either alone or together, prevented impairments significantly (P< 0.001), as there was not any significant difference between these treated lesion groups and control group. CONCLUSION: The present results suggest that CoQ10 and folic acid have therapeutic and preventive effects on cognitive impairments in Alzheimer’s disease.